Airline customer experience : digitalization in passenger services - Dutta, Pushan, 1985-; Ricciuti, Martin; Bogrekci, Ismail; Suseelan, Sumeet (Routledge, 2026)
In the 21st century, commercial aviation has been transformed into a passenger-centric business in which the customer has assumed an ever more active role in managing their own journeys. This trend is set to continue with innovations and transformations in multiple areas. Point-of-sale solutions will redefine in-flight commerce, making it easier for passengers to make purchases during their journey. Telemedicine will ensure health and safety onboard, allowing for immediate medical assistance in case of emergencies. The shift to personal electronic devices for in-flight entertainment (IFE) will cater to the digitally savvy passenger and their expectations in the digital age. Smart cabins will revolutionize in-flight food and beverage services, providing passengers with a more personalized and enjoyable experience. Data-driven catering will reduce food waste and boost profits in aviation. In short, all areas of the passenger experience will be affected by ongoing digital transformation.Airline Customer Experience: Digitalization in Passenger Services aims to show how digitalization is transforming the way the aviation industry operates, making it more efficient, profitable, and sustainable. The wide-ranging contents embrace all aspects of aviation relating to the customer experience, from purchase and pre-check-in, to the services offered to passengers in flight and beyond. The authors present a nuanced and kaleidoscopic view of the airline customer experience, which will be at once familiar and illuminating to readers.This book is an essential resource for advanced postgraduate students and researchers working in aviation, particularly those with a focus on aviation service operations management, customer services, and customer relationship management. Practicing airline managers and operators will also value the innovative insights and examples the book offers.